2018
DOI: 10.1140/epjc/s10052-018-6270-6
|View full text |Cite
|
Sign up to set email alerts
|

Accretion disks around the Gibbons–Maeda–Garfinkle–Horowitz–Strominger charged black holes

Abstract: It seems surprising that the emissivity properties of the accretion disk (à la Page and Thorne) surrounding the Gibbons-Maeda-Garfinkle-Horowitz-Strominger (GMGHS) black holes of heterotic string theory have not yet been studied. To fill this gap in the literature, we study the emissivity properties of the thin accretion disks around these black holes both in the Einstein and in the string frame using the Page-Thorne model. For illustration, we choose as a toy model a stellar-sized spherically symmetric black … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 59 publications
0
21
0
Order By: Relevance
“…Strong gravitational lensing by GMGHS black hole was explored in [38], which showed that there are few observational differences between Schwarzchild and GMGHS black holes for strong lensing. Accretion disks around GMGHS black hole was studied in [39]. Last but not least, the (in)stability under charged scalar perturbations and the existence of scalar clouds of the GMGHS black hole were studied in [40][41][42][43][44][45][46].…”
Section: Introductionmentioning
confidence: 99%
“…Strong gravitational lensing by GMGHS black hole was explored in [38], which showed that there are few observational differences between Schwarzchild and GMGHS black holes for strong lensing. Accretion disks around GMGHS black hole was studied in [39]. Last but not least, the (in)stability under charged scalar perturbations and the existence of scalar clouds of the GMGHS black hole were studied in [40][41][42][43][44][45][46].…”
Section: Introductionmentioning
confidence: 99%
“…and going over to the EF via using (11,12), we obtain a solution that we claim to be just the everywhere regular EF EBWH describing the positive mass mouth. This is given by…”
Section: Jf Brans II ←→ Ebwhmentioning
confidence: 94%
“…There could be other categories of hypothetical objects such as naked singularity (NS) and wormholes (WH) that are not ruled out either by theory or by experiment to date. On the contrary, there has been a recent surge of interest a e-mail: izmailov.ramil@gmail.com (corresponding author) in the study of their observational signatures, which include, but not limited to, the phenomena of accretion [2][3][4][5][6][7][8][9][10][11][12][13][14][15], gravitational lensing [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31], shadow cast on the background of the thin accretion flow [32][33][34][35][36][37][38][39][40][41] and gravitational waves [42][43][44][45][46][47]…”
Section: Introductionmentioning
confidence: 99%
“…Accretion disks for other compact astrophysical objects such as neutron, boson and fermion stars and gravastars have been studied in [66][67][68][69][70][71][72][73][74]. In a recent work [75], the authors have studied thin accretion disks around electrically and magnetically charged Gibbons-Maeda-Garfinkle-Horowitz-Strominger (GMGHS) black holes. Also, k α iron line analysis and continuum-fitting method are used to distinguish different astrophysical objects through their accretion disks [76][77][78][79].…”
Section: Introductionmentioning
confidence: 99%